TARGETED DRUG DELIVERY TO CANCER CELLS: ADVANCES IN NANOTECHNOLOGY - Bashyal, Sagar (Innovare Journal of Life Sciences, 2018)
Advancement in science and technology has brought a remarkable change in therapy of cancer. Particles are engineered in such a way so that they are attracted to diseased cells, which allows direct treatment of cancer cells. Drug delivery systems control the location in the body where it is released and the rate at which a drug is released. Conventional chemotherapeutic possess some serious side effects, including damage of the immune system and other various types of organs with rapidly proliferating cells due to nonspecific targeting, lack of solubility, and inability to enter the core part of the tumor which results in impaired treatment with the reduced dose and low survival rate. Nanoparticles can be programmed in such a way so that it can recognize the cancerous cells by giving selective and accurate drug delivery avoiding interaction with the healthy cells. The main aim of this review focuses on various strategies for cancer cell targeting. It also discusses specific drug delivery by nanoparticles inside the cells, illustrating many successful research in the field of cancer therapy.